Tratamiento de pacientes con hiperplasia mandibular. - Herrera Albán, Fernanda Abigail (2024)
This work aims to analyze the different treatment techniques used in patients with mandibular hyperplasia. It was carried out through a literature review based on the recommendations of the PRISMA (Preferred Reporting Items for Systemic Reviews and Meta-Analysis). In addition to evaluating the various treatment options available, the long-term results of different therapies will be determined. Finally, the effectiveness of correcting symptoms and improving quality of life will be analyzed. It used scientific articles from indexed journals through databases such as PubMed, Elsevier, Google Scholar, and Scielo in 10 years, i.e., from 2013 to 2023, where 41 quality publications were selected for the review. As a result, it was determined that surgical treatments offer better results and treatment stability, improving the patient's life quality, within these it was condillectomy and orthognathic surgery, which is complemented with orthodontics to improve the patient's occlusion, thus reducing the discomfort at the temporomandibular joint (TMJ) level. There are also therapeutic alternatives, such as hormone therapy and aromatase inhibitors, which are used in growing patients. The study examines a variety of treatments that have been shown to be effective for mandibular hyperplasia, thus improving patients' quality of life. It is crucial to remember that every patient is different, and therefore, treatment must be tailored to their specific needs and conditions. Orthognathic surgery, orthodontics, and aromatase inhibitors have all been shown to be beneficial in mitigating symptoms and improving patients' quality of life. In addition, growth hormone therapy may represent a valuable non-surgical alternative for the treatment of mandibular hyperplasia, especially in young patients who are still growing.